The advances of topology optimization techniques in orthopedic implants: A review. - Wu, Naichao; Li, Shan; Zhang, Boyan; Wang, Chenyu; Chen, Bingpeng; Han, Qing; Wang, Jincheng (Medical & Biological Engineering & Computing, 2021)
Metal implants are widely used in the treatment of orthopedic diseases. However, owing to the mismatched elastic modulus of the bone and implants, stress shielding often occurs clinically which can result in failure of the implant or fractures around the implant. Topology optimization (TO) is a technique that can provide more efficient material distribution according to the objective function under the special load and boundary conditions. Several researchers have paid close attention to TO for optimal design of orthopedic implants. Thanks to the development of additive manufacturing (AM), the complex structure of the TO design can be fabricated. This article mainly focuses on the current stage of TO technique with respect to the global layout and hierarchical structure in orthopedic implants. In each aspect, diverse implants in different orthopedic fields related to TO design are discussed. The characteristics of implants, methods of TO, validation methods of the newly designed implants, and limitations of current research have been summarized. The review concludes with future challenges and directions for research. Wang TO design of global layout and local structure of implants in diverse fields of orthopedic.